Dose escalation phase 1 study of radiotherapy in combination with anti-cytotoxic-T-lymphocyte-associated antigen 4 monoclonal antibody ipilimumab in patients with metastatic melanoma - Caroline Robert; Christine Mateus; Christophe Massard; Roger Sun; Eric Deutsch; Lydie Cassard; Rastilav Bahleda; Severine Roy; Emilie Routier; Nathalie Chaput-Gras; Caroline Caramella; Emilie Lanoy; et al. (Journal for ImmunoTherapy of Cancer)
Background A synergy between radiotherapy and anti-cytotoxic-T-lymphocyte-associated antigen 4 (anti-CTLA-4) monoclonal antibody has been demonstrated preclinically. The Mel-Ipi-Rx phase 1 study aimed to determine the maximum tolerated dose (MTD) and safety profile of radiotherapy combined with ipilimumab in patients with metastatic melanoma.Patients and methods A 3+3 dose escalation design was used with 9, 15, 18 and 24 Gy dose of radiotherapy at week 4 combined with 10 mg/kg ipilimumab every 3 weeks for four doses. Patients with evidence of clinical benefit at week 12 were eligible for maintenance with ipilimumab 10 mg/kg every 12 weeks starting at week 24 until severe toxicity or disease progression. The database lock occurred on April 30, 2019. Tumor growth rate of irradiated lesions and non-irradiated lesions were analyzed to assess the systemic immunologic antitumor response. Blood immune monitoring was performed before and during treatment to determine if radiotherapy could modify ipilimumab pharmacodynamics.Results 19 patients received ipilimumab between August 2011 and July 2015. Nine patients received the four doses of ipilimumab. All patients received the combined radiotherapy. Grade 3 adverse events occurred in nine patients, the most common being colitis and hepatitis. No drug-related death occurred. Dose limiting toxicity occurred in two of six patients in the cohort receiving 15 Gy. The MTD was 9 Gy. Two patients had complete response, three had partial response response and seven had stable disease, giving an objective response rate of 31% and a clinical benefit rate of 75% at week 24. The median duration of follow-up was 5.8 years (Q1=4.5; Q3=6.8). The median overall survival (95% CI) was estimated at 0.9 years (0.5–2). The median progression-free survival (PFS) (95% CI) was 0.4 (0.2–1.4). Radiotherapy combined with ipilimumab was associated with increased CD4+ and CD8+ICOS+ T cells. Increased CD8+ was significantly associated with PFS.Conclusion When combined with ipilimumab at 10 mg/kg, the MTD of radiotherapy was 9 Gy. This combination of ipilimumab and radiotherapy appears to be associated with antitumor activity. Increased CD8+ was significantly associated with PFS. Thus, immune biomarkers may be useful for early response evaluation.Trial registration number NCT01557114.